Application of environmentally friendly nanomaterials based on nitrogen oxide catalytic purification of automobile exhaust. (30th September 2020) - Jiang, Wenqing; Yu, Chensi
Although the existing NOx treatment technologies have achieved some results, they all have certain shortcomings. By comprehensively analysing the current research status of the application of catalysts in the treatment of nitrogen oxides, a photocatalytic oxidation reaction using mesoporous zeolite molecular sieves as the carrier, nano-transition as the co-catalyst, and nano-TiO2 as the main catalyst to degrade nitrogen oxidation in coal-fired flue gas is proposed. This material starts to purify the automobile exhaust gas immediately after it is exhausted. It has a large adsorption area and a good purification effect. This paper studies the purification efficiency of NOx in automobile exhaust gas with nano-TiO2 - loaded pavement. Purification efficiency of NOx in automobile exhaust under various influencing factors (temperature, light, etc.). This paper takes the chemical reaction mechanism and photocatalytic principle of automobile exhaust pollutants as the theoretical basis, and uses the built nano-TiO2 photocatalytic physical simulation test system to conduct multiple tests on road samples loaded with nano-TiO2 photocatalytic materials, and screen and process the test data, analyse the purification efficiency of NOx under different light, abrasion and other test conditions on the road surface loaded with nano-TiO2 photocatalytic material, and summarise the purification rule, as TiO2 photocatalytic material can be better in highway engineering, which provide a basis for a wider range of applications.